"Fresher Than You": Commercial Use of YouTube-Native Dance and Videographic Techniques - Harlig, Alexandra (The International Journal of Screendance, 2018)
This article focuses on four examples of commercial use of web-native and amateur video and dance aesthetics, including music videos and videos promoting clothing brands, and how corporate logics have adopted these genres and caused them to adapt in turn. Commercial use both subsumes and broadcasts the innovations of dance communities, amateur filmmakers, and subcultural entrepreneurs. At the same time, I argue that the possibility of greater self-control for the making and distributing of filmed popular dance in the social media context renders commercial mediation of popular dance more desirable to many communities of practice. Through looking at generic and technical attributes of the examples, I address the continued rhetorical power of binaries like amateur and professional, commercial and participatory, categories the reality of dance in social media in fact undermine. The commercial use of web-native videographic and dance styles is complicated by new opportunities for representation, remuneration, and creative control that come with the new platforms and modes of production. These music videos and advertisements transmit social media-native movement, videographic, and promotional techniques, but still do so within longstanding infrastructures that primarily benefit those with preexisting economic and cultural capital, and along lines of class and race.